Penyebaran Paham Feminisme di Media Sosial Instagram: - Putri Annisya Alfachrin; Nirwan Syafrin; Imas Kania Rahman (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study focuses of the widespread of feminism on social media, especially on @indonesiafeminis Instagram, which raises women's issues and social issues in general, including issues of consent, sexual violence and harassment, marital rape, genderless household, to issues of Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) to their followers. The method of this study is qualitative, by observing @indonesiafeminis Instagram account, face-to-face and online interviews via Direct Message on Instagram with the followers of @indonesiafeminis, and contents documentation on @indonesiafeminis Instagram which was the public discussion. This study explains that feminism which widely spread through the @indonesiafeminis Instagram is a liberal and secular Western feminism that is not accordance with religious taughts and Pancasila which every rules based on God values, in terms of normalize the feminism movement in Indonesia, consent in sexual relations, My Body My Authority (normalization of revealing clothes), to normalization the case of Lesbian, Gay, Bisexual, Transgender, and Queer (LGBTQ+) groups in religious views, which clearly inappropriate and violate religious rules by hide behind the Human Rights. Keywords: social media, feminism, instagram